Synthesis and characterization of silica nanospheres using nonsurfactant template - Misran H.; Yarmo M.A.; Ramesh S. (2023)
In the present work monodispersed silica spheres were successfully synthesized using nonsurfactant approach of neutral palm oil derived fatty alcohols based microemulsions. The resulting silica spheres have diameter in two size clusters; ca. 560 nm and ca. 700 nm, respectively. The synthesis was acomplished by using straight chain fatty alcohols in a combined approach of sol-gel and Stber method without extensive washing. Translucent nonsurfactant microemulsions containing straight chain fatty alcohols namely octyl alcohol (C8), decyl alcohol (C10) and dodecyl alcohol (C12) were successfully obtained. Short chain alcohols such as ethanol and methanol were used as co-solvent in the formation of silica spheres. Tetraethylorthosilicate were used as silica source as well as co-structure directing agent. The resulting silica spheres were successfully functionalized with octyl-4-methoxy cinnamate (OMC) as UV-absorbing compounds in a direct nonsurfactant co-condensation during the synthesis process. The technique employed was found to be most viable in producing silica spheres for applications as meta-atom in the fabrication of metamaterials. 2012 Elsevier Ltd and Techna Group S.r.l.